Cellular Concentration of Survivin and Caspase 3 in Habitual Tobacco Chewers with and without Oral Squamous Cell Carcinoma in South Indian Rural Population—A Case Control Study - Susanna Theophilus Yesupatham; C. D. Dayanand; S. M. Azeem Mohiyuddin (Diagnostics, 2022)
Background: There is paucity of data on tissue levels of Survivin and Caspase 3 in south Indian tobacco chewers with oral Squamous cell carcinoma (OSCC). Oral cancer is a rapidly growing, highly prevalent head and neck malignancy; it involves a mucosal epithelium of a buccal cavity exposed to tobacco and other carcinogens. The basis of the survival of a tumor cell or transformed normal cell into a neoplastic cell is by the suppression of apoptosis regulation. Recently, researchers have focused on Survivin, an inhibitor of apoptosis family of proteins (IAP), involved in apoptosis regulation in cancer cells targeting the executioner Caspase 3. The current study aims to quantify the cellular levels of Survivin and Caspase 3 in tobacco chewers with OSCC and in habitual tobacco chewers without OSCC, in comparison to controls. Methods: A single centric case control study included 186 study subjects, categorized into: Group I (n = 63), habitual tobacco chewers with OSCC; Group 2 (n = 63), habitual tobacco chewers without OSCC; and Group 3 (n = 63), the controls. Resected tumor tissue from Group 1 and buccal cell samples from Groups 2 and 3 were collected into phosphate buffer saline (PBS) and assayed for Survivin and Caspase 3 levels by the ELISA sandwich method. Results: The mean ± SD of the Survivin protein in Group 1 was (1670.9 ± 796.21 pg/mL); in Group 2, it was (1096.02 ± 346.17 pg/mL); and in Group 3, it was (397.5 ± 96.1 pg/mL) with a significance of p < 0.001. Similarly, the level of Caspase 3 in Group 1 was (7.48 ± 2.67 ng/mL); in Group 2, it was (8.85 ± 2.41 ng/mL); and in Group 3, it was (2.27 ± 2.24 ng/mL) with a significance of p < 0.001. Conclusion: The progressive transformation of buccal cells to neoplastic cells is evident; in the case of OSCC, this indicates that the over-expression of Survivin compared to Caspase 3 confirms the suppression and dysregulation of apoptosis.